Sobralia abadorum (Orchidaceae) - a new orchid species from Peru - Szlachetko, Dariusz; Dudek, Magdalena; Górniak, Marcin; Mytnik-Ejsmont, Joanna; Fernandez, Ricardo (Biodiversity: Research and Conservation, 2010)
Sobralia Ruiz & Pav. is one of the largest genus in Orchidaceae. It comprises about 150 species distributed from Mexico to Bolivia. In this paper, a new species of Sobralia from Peru, S. abadorum, is described and illustrated. Its taxonomic affinity is briefly discussed. An analysis of ITS sequences indicates an isolate position of this new species.